PRONUNCIATION ERRORS IN ENGLISH SPEAKING CLASS: AN APPLIED LINGUISTICS APPROACH - Ni Ketut Putri Nila Sudewi; Miswaty, Titik Ceriyani (LITERA : Jurnal Bahasa Dan Sastra, 2026)
This study aimed to investigate pronunciation errors made by fourth-semester students of the English Literature Department at Bumigora University during speaking class. A qualitative descriptive method was employed, with data collected from students’ oral descriptions of daily activities. Their speech was recorded, transcribed, and analyzed for pronunciation errors, focusing on consonants, vowels, and diphthongs. The findings revealed three major categories of errors. First, consonant errors occurred most frequently in the substitution of interdental sounds /θ/ and /ð/ with alveolar sounds /t/ and /d/. Second, vowel errors were observed in the confusion between long and short vowels, such as /iː/ and /ɪ/, and the mispronunciation of /æ/ and /e/. Third, diphthong errors appeared when students simplified diphthongs into monophthongs, such as [haʊs] pronounced as [hos]. These errors were caused by several factors, including mother tongue interference, lack of exposure to authentic English pronunciation, difficulty in perceiving phonemic contrasts, and psychological factors such as nervousness or hesitation. The study concludes that students’ pronunciation errors are not only challenges but also indicators of their interlanguage development. Error analysis, viewed through an applied linguistics approach, provides valuable insights for teachers to design corrective feedback and targeted pronunciation practice. By addressing these errors systematically, lecturers can help students improve their communicative competence and confidence in speaking English.